Design Of Single Phase Voltage Loss Relay System On Three Phase Motors At Blang Pidie Substation - Fakhrul Razi Anjas; Muhammad Erpandi Dalimunthe (INFOKUM, 2025)
Three-phase motors are one of the main equipment in the electric power system used to drive various industrial machines, including the Blang Pidie Substation. One of the problems that often occurs in three-phase motors is the loss of voltage in one phase (single phasing), which can cause current imbalance, motor temperature increase, and the potential for greater damage. Therefore, a protection system is needed that can detect the loss of single-phase voltage and automatically stop motor operation to prevent further damage. This study aims to design and build a single-phase voltage loss protection relay system on three-phase motors at the Blang Pidie Substation. This system uses a voltage relay as the main component to detect voltage loss in one phase, which will then activate the current breaking mechanism to protect the motor. Testing is carried out by simulating various voltage loss conditions to analyze the response speed and effectiveness of the relay system in protecting the motor. The results of the study show that the designed relay system is able to detect single-phase voltage loss with high accuracy and fast response time. When a disturbance occurs, the system immediately cuts off the electricity to the motor to prevent overheating and permanent damage. The implementation of this system is expected to improve the reliability of three-phase motor operations and reduce the risk of failure at the Blang Pidie Substation.